Optical determination of the Néel vector in a CuMnAs thin-film antiferromagnet - Saidl, V.; Němec, P.; Wadley, P.; Hills, V.; Campion, R.P.; Novák, V.; Edmonds, K.W.; Maccherozzi, F.; Dhesi, S.S.; Gallagher, B.L.; Trojánek, F.; Kunes, J.; et al. (Nature Publishing Group, 2017)
Recent breakthroughs in electrical detection and manipulation of antiferromagnets have opened a new avenue in the research of non-volatile spintronic devices.1-10 Antiparallel spin sublattices in antiferromagnets, producing zero dipolar fields, lead to the insensitivity to magnetic field perturbations, multi-level stability, ultrafast spin dynamics and other favorable characteristics which may find utility in fields ranging from magnetic memories to optical signal processing. However, the absence of a net magnetic moment and the ultra-short magnetization dynamics timescales make antiferromagnets notoriously difficult to study by common magnetometers or magnetic resonance techniques. In this paper we demonstrate the experimental determination of the Néel vector in a thin film of antiferromagnetic CuMnAs9,10 which is the prominent material used in the first realization of antiferromagnetic memory chips.10 We employ a femtosecond pump-probe magneto-optical experiment based on magnetic linear dichroism. This table-top optical method is considerably more accessible than the traditionally employed large scale facility techniques like neutron diffraction11 and Xray magnetic dichroism measurements.12-14 This optical technique allows an unambiguous direct determination of the Néel vector orientation in thin antiferromagnetic films utilized in devices directly from measured data without fitting to a theoretical model.